A universal of speech timing: Intonation units form low-frequency rhythms - Maya Inbar; Eitan Grossman; Ayelet N. Landau (Proceedings of the National Academy of Sciences, 2025)
Intonation units (IUs) are a hypothesized universal building block of human speech [W. Chafe, Discourse, Consciousness and Time: The Flow and Displacement of Conscious Experience in Speaking and Writing (1994); N. P. Himmelmann et al. , Phonology 35 , 207–245 (2018)). Linguistic research suggests they are found across languages and that they fulfill important communicative functions such as the pacing of ideas in discourse and swift turn-taking. We study the rate of IUs in 48 languages from every continent and from 27 distinct language families. Using an analytic method to annotate natural speech recordings, we identify a low-frequency rate of IUs across the sample, with a peak at 0.6 Hz, and little variation between sexes or across the life span. We find that IU rate is only weakly related to speech rate quantified at the syllable level, and crucially, that cross-linguistic variation in IU rate does not stem from cross-linguistic variation in syllable rate.